Decision Support System for Futsal Player Selection Using the Profile Matching Method - Hafiz, Farhan Mohammad; Rachmadi, Pratiwi; Purbaratri, Winny (Universitas Mohammad Husni Thamrin, 2025)
Futsal is a sport that is widely enjoyed by all groups. Each futsal team will open a selection process for players who want to become professional futsal players. Each team conducts a selection process to determine which players will join the core team. Player selection is a crucial aspect in shaping a team's strength and performance. Effective futsal player selection is key to forming a competitive and winning team. Selecting the right players is crucial to ensuring team performance and victory. The profile matching method is used to compare individual player profiles with the criteria set by the team for the selection process. This study aims to develop a decision support system (DSS) for selecting futsal players for the striker (pivot) position at SMA Angkasa 1 using the profile matching method. In the study, data on the futsal player selection criteria were collected from on-field assessments, skill tests, and interviews. The data used in this study included several criteria such as experience, strength, stamina, speed, and teamwork. The results of calculations using profile matching indicate the order of quality players that can be selected based on the criteria data. By creating this system, it is hoped that the futsal player selection process can be improved and result in a strong and optimal team composition, which will ultimately improve team performance in various competitions and matches.